BRIDGING THE PAST AND PRESENT: AN ANALYSIS OF SULTAN ZAINUL ABIDIN'S LEGACY THROUGH THE ZAINGAIR CANAL IN KASHMIR - Ishfaq Ahmad Mir (PT. Radja Intercontinental Publishing, 2023)
Sultan Zainul Abidin, popularly known as